February 2011: Venus rules the morning sky (Astronomy (Milwaukee), 2011)
The shadows visibility gradually decreases this month because Earth's orbital motion brings our planet closer to the line joining the Sun and Saturn. Mars passes behind the Sun from our point of view February 4; Neptune follows suit on the 17th; and Mercury completes the triple play February 25. [...] on a note of purely theoretical interest, the solar system is a bit lopsided this month.